SASTRA DAERAH BANJAR DAN MASALAH KEBHINEKAAN - Saefuddin Nfn (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
Banjar local literature is a local literature that produced by Banjar society in South Kalimantan. It can be make closer relationship among tribes, customs, cultures from all people in Indonesia that exists in Banjar society, South Kalimantan. A study about unity and diversity of Banjar local literature is an effort to strengthen NKRI (Republic of Indonesia). It is important because Indonesia chooses language as its national identity united from diversity including local literature and its development that becomes the frame of Indonesian unity in the form of unity in diversityness. The method which is used in this paper is analytic descriptive. It is hoped that this paper exposes Banjar local literature in South Kalimantan as a part of Indonesian literature in the form of unity in diversityness.